THE ROLE AND FUNCTIONS OF ASSESSMENT IN TEACHING MODERN FOREIGN LANGUAGES IN PRIMARY CLASSES - Saodat Musurmonova Jamshidovna; Ergasheva Dilzira Golib kizi (Ta’lim innovatsiyasi va integratsiyasi, 2026)
Abstract This article examines the role, functions, and importance of assessment in the process of teaching a modern foreign language in primary classes. The types of assessment, the evolution of the assessment system, and effective assessment criteria that take into account the psychological characteristics of young learners are analyzed. Special attention is paid to formative and game-based assessment as effective tools for motivation and language development.